A new genus and species of Saccharosydnini (Hemiptera: Fulgoromorpha: Delphacidae) from Argentina - Batiz, María F. Rossi; de Remes Lenicov, Ana M. M. (Zootaxa, 2011)
One new delphacid genus and species, Lacertina australis Remes Lenicov & Rossi Batiz, gen. et sp. nov. (Hemiptera: Fulgoromorpha: Delphacidae: Saccharosydnini), is described and illustrated from Argentina with distribution data and host plants data provided. The new genus is easily distinguished from all other genera of the Neotropical Saccharosydnini by being strongly dorsoventrally flattened with a wide vertex projecting 2/3 of its length beyond the eyes and the presence of two submedian carinae on frons. An identification key to the genera of Saccharosydnini is provided.